Making market information services work better for the poor in Uganda - Ferris, Shaun; Engoru, Patrick; Kaganzi, Elly (International Food Policy Research Institute, 2008)
There is growing pressure for farmers in countries such as Uganda to accelerate their efforts to commercialize production in the face of increasing market competition from neighboring countries and across the world. To assist farmers, a new generation of low cost market information services is being developed that takes advantage of information and communication technologies such as FM radios, mobile phones, and internet-based communications systems, to enable farmers to monitor and adjust to dynamic market conditions in local, national, and export markets. Although there is much interest in market information from farmers, other market chain actors, and service providers, there is skepticism from funding agencies to support such services over the long term, due to past failures. This study therefore aims to evaluate how farmers access and use market information to improve their market decision making. It also evaluates whether there are any advantages of collective action in using market information to improve marketing decisions. This is considered an important point of analysis as virtually all extension plans in Uganda currently use farmer groups as key element of their learning and intervention strategies. Survey results found that all farmers interviewed were able to access market information through radio and mobile phones. In Uganda, up to 94 percent of farmers interviewed owned a radio and 25 percent of farmers owned mobile phones. Up to 52 percent of farmers indicated that receiving Market Information Services (MIS) had a positive impact on their business, and 39 percent stated that it had a lot of impact in terms of decision making and stabilizing incomes.